Home, Pre-school and Primary school influences upon children's educational attainment at age 11 - Edward Melhuish; Pam Sammons; Kathy Sylva; Iram Siraj-Blatchford; Brenda Taggart (Arizona State University, 2014)
This paper examines the benefits of Pre-school centre experience in disadvantaged children's school readiness, educational achievements and social adjustment. In this article, we describe findings from a large-scale longitudinal study in England that provides evidence on the contribution of home, pre-school and primary school to children's development, a unique evidence for a sample that is close to nationally representative rather than for disadvantaged groups only and thus provides stronger evidence relevant to the issue of the benefits that might accrue generally from universal pre-school provision. Data from this study can be used to look at the relative benefits accruing from home, pre-school and school influences for the general population, and the relative magnitude of the benefits associated with variation in home, pre-school and school environments.